PERHITUNGAN PREMI ASURANSI PERTANIAN PADA TANAMAN PADI DI PROVINSI LAMPUNG - Rivai, Muklas; Ratam, Aldila Nur Indah Berliana; Marisa; Madonna, Nora; Simanjuntak, Erica Grace; Gustina K.S, Annisa Hevita; Mahkya, Dani Al; Rosni; Dewi, Karina Sylfia; Azzanina, Nanda; Nasrullah; Hayati, Ma’rufah; et al. (Nusantara Hasana Journal, 2025)
This research aims to calculate agricultural insurance premiums for rice crops in Lampung Province using the Black–Scholes model approach. The background of the study lies in the high production risks caused by climate variability, extreme weather, flooding, drought, and pest attacks, all of which significantly affect the potential for crop failure. Secondary data in the form of harvested area and rice production for the 2019–2023 period were obtained from official publications of the Statistics Indonesia. The analysis shows that rice yield per hectare follows a lognormal distribution based on the Kolmogorov–Smirnov test, thus meeting the fundamental assumptions of the model. Calculation parameters, including production volatility, risk-free interest rate, threshold value, and production time, were used in estimating the premium. The results indicate that the probability of production falling below the threshold is 13.69%, while the calculated premium is IDR 802,584 per planting season. These findings confirm that the Black–Scholes model can be applied as an objective quantitative approach to determining risk-based agricultural insurance premiums. The application of this method has the potential to improve the accuracy of premium calculations and support the development of a fairer and more sustainable Rice Farming Insurance Scheme (AUTP).